2005
DOI: 10.1089/jwh.2005.14.515
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Complications of Induced Abortions in Nigeria

Abstract: Policies and programs should address improving abortion practices and postabortion care, increasing contraceptive use, and reducing the practice of female circumcision.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
14
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 16 publications
4
14
0
Order By: Relevance
“…A significant correlation with celibacy or separated or divorced women or widow was also observed in the present study, and these results corroborate those reported by many other authors [10, 11, 13, 16, 20–22]. These results differ from those of some authors who found a significant correlation with marriage or cohabitation: for example, in 2014 Dragoman’s secondary analysis of data from the World Health Organization (WHO), that may be correlated to the probable confusion that would be induced by cases of complications resulting from spontaneous abortions that had not been discriminated against in the database [15]; Igberase, at a tertiary hospital located in rural Nigeria [12], that may reflect possible rural realities; Shah at a University Hospital in Pakistan, and Erfani in Tehran, Iran [23, 24].…”
Section: Discussionsupporting
confidence: 94%
“…A significant correlation with celibacy or separated or divorced women or widow was also observed in the present study, and these results corroborate those reported by many other authors [10, 11, 13, 16, 20–22]. These results differ from those of some authors who found a significant correlation with marriage or cohabitation: for example, in 2014 Dragoman’s secondary analysis of data from the World Health Organization (WHO), that may be correlated to the probable confusion that would be induced by cases of complications resulting from spontaneous abortions that had not been discriminated against in the database [15]; Igberase, at a tertiary hospital located in rural Nigeria [12], that may reflect possible rural realities; Shah at a University Hospital in Pakistan, and Erfani in Tehran, Iran [23, 24].…”
Section: Discussionsupporting
confidence: 94%
“…Mitsunaga et al in their review of risk factors for complications of abortion in south western Nigeria identified haemorrhage among the common post abortal complication amongst patients seen. 8 However, other studies identified sepsis as the commonest post abortal complication. 9 - 11 …”
Section: Discussionmentioning
confidence: 99%
“…The immediate complications of abortion, namely heavy bleeding and infection have been recognized as important factors that contribute to increase in maternal mortality and morbidity due to abortion. 3,6 these complications have also been identified to occur more with abortions that are induced unsafely. 3 Each year, approximately 20 million unsafe abortions are performed worldwide.…”
Section: Introductionmentioning
confidence: 99%